Antibacterial Potential of Selected Herbs and Spices against Human Pathogenic Bacteria - Jamuna Prakash, Prof (International Journal of Pharmaceutical & Biological Archive, 2014)
Antibacterial Potential of Selected Herbs and Spices against Human Pathogenic Bacteria